Introducing Digital Marketing To Expand Marketing For MSME Players In Hamlet 3 Mekkaraya, Kersamanah District, Garut Regency - Galih Abdul Fatah Maulani; Muhammad Husna Nugraha; Melisa Amelia Putri (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstrak This activity aims to introduce digital marketing in order to expand business actors in Hamlet 3 Mekkaraya, Kersamanah District, Garut Regency. By using the method of explanation, discussion and practice. The explanation method is carried out by conveying material related to digital marketing directly to MSME actors. Discussion method, interaction between two or more people who discuss basic science. This method is to facilitate MSME actors who want to ask for material that has not been understood. In the practical method of implementation by applying the knowledge that they already have, namely practicing how to use online media as a means of product marketing. The results in the activity show that efforts to expand value marketing for MSME actors through digital marketing are focused on 5 things, namely problem identification, the importance of branding and business legality, product packaging, e-commerce account creation and product advertising, digital marketing. Abstract Dalam Kegiatan ini bertujuan untuk Memperkenalkan Digital marketing guna memperluas pelaku usaha Di Dusun 3 Mekkaraya Kecamatan Kersamanah Kabupaten Garut .Dengan menggunakan metode penjelasan,diskusi dan praktik. Metode penjelasan dilakukan dengan menyampaikan materi terkait digital marketing secara langsung kepada pelaku UMKM. Metode diskusi, interaksi antara dua orang atau lebih yang membahas ilmu pengetahuan dasar. Metode ini untuk memfasilitasi pelaku UMKM yang ingin menanyakan materi yang belum dipahami. Pada metode praktik pelaksanaannya dengan menerapkan ilmu pengetahuan yang telah dimiliki, yaitu mempraktikkan cara penggunanaan media daring sebagai sarana pemasaran produk. Hasil dalam kegiatan menunjukkan bahwa upaya dalam memperluas pemasaran nilai bagi pelaku UMKM melalui digital marketing dititik beratkan pada 5 hal, yaitu identifikasi masalah, pentingnya branding dan legalitas usaha, pengemasan produk, Pembuatan akun e-commerce dan iklan produk, digital marketing.